2021
DOI: 10.1007/s42972-021-00040-3
|View full text |Cite
|
Sign up to set email alerts
|

Rent Burden and Depression Among Mothers: an Analysis of Primary Caregiver Outcomes

Abstract: Using national longitudinal survey data from the Fragile Families & Child Wellbeing Study (FFCWS), this study builds on existing knowledge about housing insecurity, female caregivers, and well-being. The study analyzed the relationship between housing cost burdens (HCB) and depression among a sample ( N = 399) of predominantly (67.6%) Black non-Hispanic mothers and other female primary caregivers. A generalized estimating equation (GEE) model yielded results that indicate housing cost bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Only one study, conducted by Rodgers et al (2019), analyzed the general population of renters, while another study, by Mason et al (2013), conducted an additional analysis investigating high-income renters; both studies found no association. Among the findings specific to low-income renters, six showed statistical significance (Arundel et al, 2022; Baker et al, 2019; Baker, Lester, et al, 2020; Elliott et al, 2021; Mason et al, 2013; Reeves et al, 2016), whereas two yielded non-significant results (Chambers et al, 2015; Prentice & Scutella, 2020).…”
Section: Evidence Synthesismentioning
confidence: 94%
See 4 more Smart Citations
“…Only one study, conducted by Rodgers et al (2019), analyzed the general population of renters, while another study, by Mason et al (2013), conducted an additional analysis investigating high-income renters; both studies found no association. Among the findings specific to low-income renters, six showed statistical significance (Arundel et al, 2022; Baker et al, 2019; Baker, Lester, et al, 2020; Elliott et al, 2021; Mason et al, 2013; Reeves et al, 2016), whereas two yielded non-significant results (Chambers et al, 2015; Prentice & Scutella, 2020).…”
Section: Evidence Synthesismentioning
confidence: 94%
“…Housing cost burden in a low-income sample (equivalent to '30/40' measure) Bentley et al, (2016); Elliott et al (2021) Housing affordability stress/ '30/40' measure Arundel et al (2022); Mason et al (2013) Housing affordability stress pattern Aggregated housing cost burden Rodgers et al (2019) Amount of 'out-of-pocket rent'/ residual income Amount of housing benefits Reeves et al (2016) Receiving housing assistance Chambers et al (2015) Living in social housing Prentice & Scutella ( 2020)…”
Section: Rent/income Ratiomentioning
confidence: 99%
See 3 more Smart Citations